Cloud Migration Blueprinting and Integration Governance Frameworks: A Structured Approach to Enterprise Architectural Transformation - Saravanan Palaniappan (International Journal of Computational and Experimental Science and Engineering, 2026)
From a fairly basic technical task to a highly complex architectural problem requiring appropriate governance, precise semantics, and operational stability, cloud migration has undergone significant changes. Despite the cutting-edge automation systems and cloud-native solutions available, companies still struggle to create effective migration architectures, maintain reliable data integration, and ensure uniform governance across multiple hybrid and multi-cloud environments. The following paper proposes a comprehensive Cloud Migration Blueprinting and Integration Governance Framework that organizes decision-making, aligns architectural designs with corporate policies, and embeds governance principles directly into migration processes. The framework combines reference architecture modeling, metadata-driven integration controls, and policy-aware orchestration to reduce confusion, expedite migration preparation, and enhance tracking of data movement and transformation across cloud ecosystems. The model redefines how architects operate—not just as solution designers, but as governance enforcers who ensure that integration principles, compliance constraints, and lineage accountability are built in from the first blueprint sketch to final execution.